Perlindungan Hukum Terhadap Nasabah Dalam Akad Murabahah Pada Bank Syariah Di Magelang - Himmatul Aliyah; R Murjiyanto; Sunarya Raharja (Kajian Hasil Penelitian Hukum, 2020)
Murabaha contract is a contract of buying and selling goods by stating the acquisition price and profit margin agreed by the seller and buyer. The mechanism for determining customers is found to have turned out to be different operating standards between Islamic banks. As the results of research murabaha contract clause on Islamic banks in Magelang. There are at least two ways, namely through the determination of the court and through the determination based on the contract clause. This research is an empirical normative legal research that uses literature studies and field studies at PT. Magelang State Savings Bank and PT. Islamic People's Financing Bank Meru Sankara Magelang. Savings on problematic financing as a form of legal protection for sharia banking customers can be done by several methods, namely: rescheduling, reconditioning, restructuring, combination and executing collateral sale of collateral through auction. There are 5  forms of legal protection for sharia banking customers in Murabaha contract, namely: protection of sharia principles and usury practices, protection from manipulation of financing agreements, protection from takwid  takzir expenses and financing risks, protection of financial guarantees from insurance companies, and protection in financing contract disputes.